Aluminoborosilicate glass compositions for display applications and products comprising same

By developing aluminoborosilicate glass compositions and optimizing their composition and properties, we address the thermal and mechanical property challenges of glass compositions in high-resolution display manufacturing, achieving high annealing points, low stress optical coefficients and dimensional stability , suitable for 8K display technology.

CN119330582APending Publication Date: 2025-01-21CORNING INC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410967872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-07
Filing Date
2024-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing glass compositions face challenges in the manufacture of high resolution displays, especially in 8K display technology, which requires high annealing points, low stress optical coefficients and dimensional stability while avoiding metal ions diffusion. The transistor is damaged.

Method used

An aluminoborosilicate glass composition was developed containing alkaline earth metal oxides, low concentrations of boron oxide and strontium oxide. The glass was optimized by adjusting the proportions of ingredients such as SiO2, Al2O3, B2O3, MgO, CaO, SrO and BaO. physical and chemical properties.

Benefits of technology

It achieves a high annealing point, low stress optical coefficient and desired liquid viscosity, making it suitable for ultra-high resolution display applications under 8K display technology and reducing the risk of metal ion diffusion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330582A_ABST
    Figure CN119330582A_ABST
Patent Text Reader

Abstract

Aluminoborosilicate glass compositions, products including the same, methods of making the same, and methods of using the same are provided. Such glass compositions include an alkaline earth metal oxide. The glass composition includes low concentrations of boron oxide and strontium oxide. Such glass compositions may be substantially alkali free. The glass compositions exhibit desirable physical and chemical properties, such as high annealing point, high modulus of elasticity, low stress optical coefficient (SOC), low T (35kP) and T (200P), and desirable liquid phase viscosity. The glass composition is suitable for use as a substrate in a flat panel display device having ultra-high resolution, such as an active matrix liquid crystal display (AMLCD).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority benefit of U.S. Provisional Application Serial No. 63 / 562,453 filed on March 7, 2024 under the Patent Act, and also claims the priority benefit of U.S. Application No. 18 / 224,780 filed on July 21, 2023 under the Patent Act, and the said application claims the priority benefit of U.S. Provisional Application Serial No. 63 / 527,367 filed on July 18, 2023 under the Patent Act, the contents of which are relied upon by this application and are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates generally to glass compositions. More particularly, the disclosed subject matter relates to glass compositions having good properties and suitable for display applications; articles containing the glass compositions; and methods of making the same. Background Art

[0004] Planar or curved substrates made of optically transparent materials such as glass are used in flat panel displays, photovoltaic devices, and other suitable applications. In addition to the requirements for optical transparency, glass compositions also need to meet different challenges depending on the manufacturing process and application.

[0005] For example, the production of liquid crystal displays such as active matrix liquid crystal display devices (AMLCD) is complex, and the properties of the substrate glass are very important. The physical dimensions of the glass substrates used in the production of AMLCD devices need to be strictly controlled. The pull-down sheet drawing process, and in particular the fusion process, can produce glass sheets that can be used as substrates without the need for expensive post-forming finishing operations such as grinding and polishing. However, the fusion process has quite strict restrictions on the properties of the glass, which requires a relatively high liquidus viscosity.

[0006] In the field of liquid crystal displays, it is preferred to use thin film transistors (TFTs) based on polycrystalline silicon because they are able to transport electrons more efficiently. Polycrystalline silicon-based transistors (p-Si) are characterized by having a higher mobility than those based on amorphous silicon (a-Si). This makes it possible to manufacture smaller and faster transistors, ultimately producing brighter and faster displays. One problem with p-Si-based transistors is that their manufacture requires higher process temperatures than those used in the manufacture of a-Si transistors. These temperatures are in the range of 450°C to 600°C, compared to the 350°C peak temperature used in the manufacture of a-Si transistors.

[0007] Glass compositions for display applications need to have good thermal and mechanical properties as well as dimensional stability that meet processing and performance requirements. In addition, diffusion of metal ions into thin film transistors may also damage the transistors. Such diffusion needs to be avoided.

[0008] Display technologies such as TV monitors are moving towards 8K technology. 8K refers to a horizontal resolution of the order of 8,000 pixels. For example, when an 8K TV has a screen with 7,680 horizontal pixels and 4,320 vertical pixels, such a TV may have a total of about 33 million pixels. 8K technology provides ultra-high resolution. 8K TVs have four times the pixels of 4K TVs with ultra-high definition (UHD) resolution, so the picture quality is clearer and more detailed. Summary of the invention

[0009] The present disclosure provides a glass composition, a product containing the glass composition, a method of making the glass composition and the product, and a method of using the glass composition and the product. The glass composition is an aluminoborosilicate glass and includes an oxide of an alkaline earth metal and a low concentration of boron oxide and strontium oxide.

[0010] Such glass compositions may be substantially alkali-free. The glass compositions exhibit desirable physical and chemical properties, such as high annealing point, high elastic modulus, low stress optical coefficient (SOC), low T (35 kP) and T (200 P), and desirable liquidus viscosity. The glass compositions are suitable for use as substrates for display applications with ultra-high resolution, such as flat panel display devices.

[0011] In one aspect, the present disclosure provides a glass or a glass composition.

[0012] According to some embodiments, the glasses or glass compositions provided herein include the following substances in mole percentages on an oxide basis:

[0013] SiO2: 66.17-74.31;

[0014] Al2O3: 11.72-13.86;

[0015] B2O3: 0.71-1.75;

[0016] MgO: 4.61-6.36;

[0017] CaO: 4.81-7.27;

[0018] SrO: 0.10-1.42; and

[0019] BaO:2.38-4.00.

[0020] According to some embodiments, the glasses or glass compositions provided herein include the following substances in mole percentages on an oxide basis:

[0021] SiO2: 69.65-70.77;

[0022] Al2O3: 12.34-13.20;

[0023] B2O3: 0.75-1.67;

[0024] MgO: 4.85-6.06;

[0025] CaO: 5.06-6.92;

[0026] SrO: 0.11-1.35; and

[0027] BaO:2.51-3.81.

[0028] The glass composition may include an alkali metal oxide in an impurity amount. In some embodiments, the glass composition or glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O, and K2O of less than 0.1 mol.%, such as less than 0.09 mol.%, less than 0.08 mol.%, less than 0.07 mol.%, less than 0.06 mol.%, less than 0.05 mol.%, less than 0.04 mol.%, less than 0.03 mol.%, less than 0.02%, less than 0.01%, or 0%. In some embodiments, the glass composition has a combined concentration of Li2O, Na2O, and K2O of less than 0.06 mol.%.

[0029] In some embodiments, B2O3 is in a suitable range. For example, B2O3 is in the range of 0.75 to 1.75 mole percent, in the range of 0.75 to 1.67 mole percent, in the range of 0.75 to 1.60 mole percent, in the range of 0.75 to 1.50 mole percent, in the range of 0.75 to 1.40 mole percent, in the range of 0.75 to 1.30 mole percent, in the range of 0.75 to 1.20 mole percent, or in the range of 0.75 to 1.00 mole percent. In some embodiments, B2O3 is in the range of 0.75 to 1.00 mole percent.

[0030] In some embodiments, SrO is within a suitable range. For example, SrO is within a range of 0.11 to 1.42 mole percent, within a range of 0.11 to 1.40 mole percent, within a range of 0.11 to 1.35 mole percent, within a range of 0.11 to 1.30 mole percent, within a range of 0.11 to 1.20 mole percent, within a range of 0.11 to 1.10 mole percent, within a range of 0.11 to 1.00 mole percent, within a range of 0.11 to 0.90 mole percent, within a range of 0.11 to 0.80 mole percent, within a range of 0.11 to 0.70 mole percent, within a range of 0.11 to 0.60 mole percent, within a range of 0.11 to 0.50 mole percent, within a range of 0.11 to 0.40 mole percent, within a range of 0.11 to 0.30 mole percent, or within a range of 0.11 to 0.20 mole percent. In some embodiments, SrO is in the range of 0.11 to 1.00 or 0.50 mole percent.

[0031] In some embodiments, the ratio of RO / Al2O3 is in the range of 1.13 to 1.31, and RO is the sum of the molar percentages of MgO, CaO, SrO, and BaO. For example, in some embodiments, the ratio of RO / Al2O3 is in the range of 1.20 to 1.31.

[0032] The glass may further comprise 0.01 mol.% to 0.4 mol.% of a chemical fining agent selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br, or any combination thereof. For example, in some embodiments, the chemical fining agent comprises 0.08 mol.% to 0.14 mol.% SnO2.

[0033] In some embodiments, the glass composition may include impurity amounts of Fe2O3, ZrO2, or TiO2. Each of Fe2O3, ZrO2, and TiO2 may be in the range of 0 to 0.03 mole percent. In some embodiments, each of Fe2O3, ZrO2, and TiO2 may be zero or less than 0.01 mole percent.

[0034] The glass has a high annealing point, for example above 775° C. In some embodiments, the annealing point of the glass is in the range of 790° C. to 810° C., for example in the range of 790° C. to 806° C.

[0035] Glass also has a high elastic modulus (Young's modulus). For example, in some embodiments, the elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa.

[0036] The glass has a desirable low stress optical coefficient (SOC). For example, the SOC of the glass provided by the present disclosure is in the range of 26.70 to 30.59, such as in the range of 28.10 to 29.13 in some embodiments.

[0037] The glass also has desirable low T(35kP) and T(200P) temperatures. For example, in some embodiments, the glass has a T(35kP) in the range of 1,280°C to 1,292°C, and a T(200P) in the range of 1,654°C to 1,666°C. T(35kP) and T(200P) represent the temperatures at which the viscosity of the glass is 35 kilopoise (kP) and 200 poise (P), respectively.

[0038] According to some embodiments, the glass provided by the present disclosure is an aluminoborosilicate glass and comprises the following substances in mole percentages on an oxide basis:

[0039] SiO2: 66.17-74.31;

[0040] Al2O3: 11.72-13.86;

[0041] B2O3: 0.75-1.20;

[0042] MgO: 4.61-6.36;

[0043] CaO: 4.81-7.27;

[0044] SrO: 0.11-0.5; and

[0045] BaO:2.38-4.00.

[0046] The elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa, and the stress optical coefficient (SOC) of the glass is in the range of 26.70 to 30.59.

[0047] According to some embodiments, the present disclosure provides glasses comprising the following substances in mole percentages on an oxide basis:

[0048] SiO2: 69.65-70.77;

[0049] Al2O3: 12.34-13.20;

[0050] B2O3: 0.75-1.20;

[0051] MgO: 4.85-6.06;

[0052] CaO: 5.06-6.92;

[0053] SrO: 0.11-0.5; and

[0054] BaO:2.51-3.81.

[0055] The glass is substantially alkali-free. In some embodiments, the glass composition has a combined concentration of Li2O, Na2O, and K2O of less than 0.06 mol.%.

[0056] In some embodiments, B2O3 is in the range of 0.75 to 1.20, such as 0.75 to 1.00 mole percent. SrO is in the range of 0.11 to 1.00, such as 0.11 to 0.50 mole percent.

[0057] The RO / Al2O3 ratio of the glass is in the range of 1.14 to 1.31, for example 1.20 to 1.31, and RO is the sum of the mole percentages of MgO, CaO, SrO and BaO.

[0058] The glass also includes 0.08 mol.% to 0.14 mol.% SnO2 as a chemical fining agent. In some embodiments, the glass composition may include impurity amounts of Fe2O3, ZrO2, or TiO2. Each of Fe2O3, ZrO2, and TiO2 may be in the range of 0 to 0.03 mol percent. In some embodiments, each of Fe2O3, ZrO2, and TiO2 may be zero or less than 0.01 mol percent.

[0059] The annealing point of the glass is in the range of 790° C. to 810° C., for example, in the range of 799° C. to 806° C. The elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa, and the stress optical coefficient (SOC) is in the range of 28.10 to 29.13.

[0060] In some embodiments, the glass has a T(35kP) in the range of 1,280°C to 1,292°C, and a T(200P) in the range of 1,654°C to 1,666°C.

[0061] In another aspect, the present disclosure provides an article comprising the glass or glass composition described herein. For example, a substrate for a liquid crystal display includes the glass or glass composition described herein.

[0062] In another aspect, the present disclosure provides a flat panel display device comprising at least one plate comprising the glass as described herein. Such a device may also include a polysilicon thin film transistor.

[0063] In another aspect, a method for producing a glass or glass composition as described herein is provided. Such a method comprises at least one step of mixing and melting raw materials in mole percentages based on oxides to provide the oxides. Such a method may also comprise making a sheet comprising the glass composition by a down-drawn sheet manufacturing process or a fusion process.

[0064] The glass composition exhibits desirable physical and chemical properties. For example, the glass provided by the present disclosure has a high annealing point (e.g., above 790° C.), a low stress optical coefficient (SOC), and a desirable liquidus viscosity. TM The glass described herein has an improved elastic modulus, and a lower T(350kP), T(35kP) and / or T(200P) temperature compared to NXT glass. The glass can be manufactured at a lower cost. The glass composition is suitable for use as a substrate in a flat panel display device such as an active matrix liquid crystal display (AMLCD) with ultra-high resolution under, for example, 8K display technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] The present disclosure may be best understood when the following detailed description is read in conjunction with the accompanying drawings. It should be emphasized that, according to convention, the various features of the drawings are not necessarily drawn to scale. On the contrary, the sizes of the various features are arbitrarily enlarged or reduced for clarity. Throughout the specification and drawings, the same reference numerals represent the same features.

[0066] Figure 1 Annealing point results are shown for different mole percentages of B2O3 in glass compositions according to some embodiments. DETAILED DESCRIPTION

[0067] This description of the exemplary embodiments is intended to be read in conjunction with the accompanying drawings, which are to be considered a part of the entire written specification. In the description, relative terms such as "lower", "upper", "horizontal", "vertical", "above", "below", "upward", "downward", "top", and "bottom" and their derivatives (e.g., "horizontally", "downwardly", "upwardly", etc.) should be interpreted as referring to the orientation shown in the drawings described or discussed subsequently. These relative terms are for convenience of description and do not require that the device be constructed or operated in a particular orientation. Terms related to attachment, connection, etc., such as "connected" and "interconnected" refer to relationships in which structures are fastened or attached to each other directly or indirectly through intervening structures, as well as removable or rigid attachments or relationships, unless otherwise explicitly described.

[0068] For the purposes of the following description, it should be understood that the embodiments described below may employ alternative variations and embodiments. It should also be understood that the specific articles, compositions and / or processes described herein are exemplary and should not be considered limiting.

[0069] Open-ended terms such as "include," "including," "contain," "containing," and the like mean "comprising." These open transition phrases are used to introduce an open list of elements, method steps, and the like, and do not exclude additional, uncited elements or method steps. It should be understood that wherever an embodiment is described with the language "comprising," additional similar embodiments described with the terms "consisting of" and / or "consisting essentially of" are also provided.

[0070] The transitional phrase "consisting of" and variations thereof exclude any unrecited elements, steps, or ingredients, except for impurities normally associated therewith.

[0071] The transitional phrase "consists essentially of" or variations such as "consist essentially of" or "consisting essentially of" excludes any unrecited elements, steps, or ingredients, except those that do not materially change the basic or novel properties of the specified method, structure, or composition.

[0072] Unless the context clearly indicates otherwise, in the present disclosure, the singular forms "one", "a kind of" and "the" include plural references, and references to specific numerical values ​​include at least that specific value. When a value is expressed as an approximation by using the antecedent "about", it should be understood that the specific value forms another embodiment. As used herein, "about X" (wherein X is a numerical value) preferably refers to ±10% (including the end value) of the quoted value. For example, the phrase "about 8" preferably refers to a value (including the end value) of 7.2 to 8.8. When present, all ranges are included and can be combined. For example, when quoting a range of "1 to 5", the quoted range should be understood to include a range of "1 to 4", "1 to 3", "1-2", "1-2 and 4-5", "1-3 and 5", "2-5" and the like. In addition, when a list of alternatives is actively provided, such a list can be interpreted as indicating that any alternative can be excluded, for example, by a negative restriction in the claims. For example, when reciting a range of "1 to 5", the recited range may be understood to include any of 1, 2, 3, 4, or 5 that are negatively excluded; thus, the recitation of "1 to 5" may be understood as "1 and 3-5, but not 2", or simply "where 2 is not included". It is intended that any component, element, attribute, or step positively recited herein may be explicitly excluded in the claims, regardless of whether such component, element, attribute, or step is listed as an alternative or recited separately.

[0073] As used herein, the terms "substantially," "substantially," and variations thereof are intended to indicate that the feature being described is equal to or approximately equal to a certain value or description. Additionally, "substantially similar" is intended to mean that two values ​​are equal or approximately equal. In some embodiments, "substantially similar" may mean that the values ​​are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.

[0074] The present disclosure provides aluminoborosilicate glass compositions, products (such as articles or devices) containing the same, and methods of making the glass compositions and products. Such glass compositions include alkaline earth metal oxides. The glass compositions include low or ultra-low concentrations of boron oxide and strontium oxide. For example, the boron oxide is in the range of 0.71 to 1.75 mole percent. The strontium oxide is in the range of 0.10 to 1.40 mole percent. In some embodiments, such glass compositions are substantially alkali-free.

[0075] The glass composition exhibits desirable physical and chemical properties, such as a high annealing point, a high elastic modulus, a low stress optical coefficient (SOC), a low T(35kP) and T(200P), and a desired liquidus viscosity. In the case of low or ultra-low concentrations of boron oxide and strontium oxide, the glass composition provides a high annealing point and relatively low T(35kP) and T(200P), thereby facilitating manufacturing. When the RO / Al2O3 ratio is low, such as in the range of 1.14 to 1.31, the glass composition with a low content of boron oxide and strontium oxide provides a very high modulus and a low SOC. In addition, the glass also maintains or improves the total pitch variation (TPV). Lower T(35kP) and T(200P) provide significant advantages in manufacturing. A higher elastic modulus provides significant benefits for some applications because it increases the stiffness of the sheet during subsequent processing and helps improve TPV. A lower SOC helps reduce or eliminate MURA effects, uneven brightness, or light leakage defects that may be observed in the final display. The glass composition is suitable for use as a substrate for display applications with ultra-high resolution such as flat panel display devices.

[0076] In some embodiments, the substrate is optically transparent.Examples of substrates include, but are not limited to, flat or curved glass plates.

[0077] Unless otherwise expressly stated, the terms "glass article" or "glass" as used herein should be understood to cover any object made entirely or partially of glass. Glass articles include monolithic substrates, or laminates of glass and glass, glass and non-glass materials, glass and crystalline materials, and glass and glass ceramics (including amorphous and crystalline phases). Unless otherwise expressly stated, the terms "glass" and "glass composition" as used herein are interchangeable.

[0078] Glass articles such as glass sheets can be flat or curved and transparent or substantially transparent. As used herein, the term "transparent" is intended to mean that the transmittance of an article having a thickness of about 1 mm in the visible region of the spectrum (400-700 nm) is greater than about 85%. For example, an exemplary transparent glass sheet may have a transmittance greater than about 85% in the visible light range, such as a transmittance greater than about 90%, greater than about 95%, or greater than about 99%, including all ranges and sub-ranges therebetween. According to various embodiments, the transmittance of the glass article in the visible light region may be less than about 50%, such as less than about 45%, less than about 40%, less than about 35%, less than about 30%, less than about 25%, or less than about 20%, including all ranges and sub-ranges therebetween. In certain embodiments, the exemplary glass sheet may have a transmittance greater than about 50% in the ultraviolet (UV) region (100-400 nm), such as greater than about 55%, greater than about 60%, greater than about 65%, greater than about 70%, greater than about 75%, greater than about 80%, greater than about 85%, greater than about 90%, greater than about 95%, or greater than about 99%, including all ranges and sub-ranges therebetween.

[0079] Exemplary glasses include, but are not limited to, aluminoborosilicates having compositions as described herein. The glass articles may optionally be strengthened. In some embodiments, the glass articles may be mechanically strengthened by exploiting the mismatch in thermal expansion coefficients between portions of the glass article to create regions of compressive stress and a central region exhibiting tensile stress. In some embodiments, the glass articles may be thermally strengthened by heating the glass to a temperature above the glass transition point and then rapidly quenching. In some other embodiments, the glass articles may be chemically strengthened by ion exchange.

[0080] In the embodiments of the glass compositions described herein, unless otherwise specified, the concentrations of constituent components (eg, SiO 2 , Al 2 O 3 , etc.) are expressed as mole percent (mol. %) on an oxide basis.

[0081] The terms "free" and "substantially free" when used to describe the concentration and / or absence of a particular constituent in a glass composition mean that the constituent is not intentionally added to the glass composition. However, the glass composition may contain trace amounts of the constituent as a contaminant or impurity, in an amount of less than 0.03 mol.% or less than 0.01 mol.%.

[0082] In some embodiments, the glass compositions provided herein are alkali-free or substantially alkali-free. Unless otherwise expressly stated, the terms "alkali-free" or "substantially alkali-free" for glass compositions used herein should be understood to encompass glass compositions having a combined concentration of Li2O, Na2O, and K2O of less than 0.1 mol.%, such as less than 0.06 mol.%, less than 0.05 mol.%, less than 0.02 mol.%, less than 0.01 mol.%, or 0 mol.%.

[0083] The term "impurity level" as used herein is understood to be trace amounts of oxides that are not added to the formulation, but sometimes such trace amounts may be introduced into the formulation from processing equipment or other added ingredients containing trace impurities. Impurity levels are understood to encompass "substantially free" or "free".

[0084] In the glass compositions described herein, the ratio of RO / Al2O3 is the ratio of the sum of the RO mole percentages to the Al2O3 mole percentage, where RO includes MgO, CaO, SrO, BaO, and ZnO. When the composition does not contain ZnO, RO refers to the mole percentage of the alkaline earth metal oxide, and the ratio of RO / Al2O3 is the same as the ratio of (MgO+CaO+SrO+BaO) / Al2O3. In some embodiments, the glass contains no ZnO or contains only an impurity amount of ZnO.

[0085] As used herein, the term "softening point" refers to the viscosity of a glass composition at 1×10 7.6 The temperature during parking.

[0086] As used herein, the term "annealing point" refers to the viscosity of the glass composition at 1×10 13 The temperature during parking.

[0087] As used herein, the terms "strain point" and "T 应变 " refers to the viscosity of the glass composition of 3 × 10 14 The temperature during parking.

[0088] The liquidus temperature of glass (T liq ) is the temperature (°C) above which no crystalline phase can coexist in equilibrium with the glass. The liquidus viscosity is the viscosity of the glass at the liquidus temperature.

[0089] As used herein, the term "CTE" refers to the coefficient of thermal expansion of a glass composition in the temperature range of about room temperature (RT) to about 300°C. The linear coefficient of thermal expansion (CTE) in the temperature range of 25-300°C is expressed in ×10 -7 / ℃ and measured according to ASTM standard E228.

[0090] Young's modulus values ​​and shear modulus (in GPa) and Poisson's ratio are determined using a resonant ultrasonic spectroscopy technique of the general type specified in ASTM E1875-00e1. The terms "Young's modulus" and "elastic modulus" are interchangeable.

[0091] Fracture toughness can be measured using methods known in the art, for example, using a chevron notch, a short bar, a notched beam, etc., in accordance with ASTM C1421-10, "Standard Test Methods for Determination of Fracture Toughness of Advanced Ceramics at Ambient Temperature".

[0092] Stress-optical coefficient (SOC) values ​​may be measured as described in Procedure C (Glass Disk Method) of ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient."

[0093] As the industry moves toward 8K display panels, thicker copper wires will be required. Copper has a high CTE, and thicker copper wires will result in higher tensile film stress, causing both the sheet and the panel to warp. This can interfere with processing yields. Referring to Stoney's formula shown in Equation 1 below,

[0094]

[0095] R is the radius of curvature, E is Young's modulus, t is the cantilever thickness, is Poisson's ratio, and σ is the resulting surface stress.

[0096] It can be seen that the amount of strain is proportional to E (elastic modulus). Therefore, for a given stress, a higher modulus (E) will result in lower strain / warp.

[0097] In addition, panel manufacturers are moving toward borderless panel designs, which leads to excessive stress-induced light leakage (mura). The mura intensity is related to the glass stress optical coefficient (SOC) through Equation 2:

[0098] Mura intensity ∝(SCO X t) 2 (Formula 2),

[0099] where t is the thickness of the glass sheet.

[0100] It is expected that the reduction in glass SOC will lead to an improvement in mura or a reduction in light leakage.

[0101] In the present disclosure, the glass is designed to increase physical properties such as Young's modulus and reduce stress optical coefficient (SOC). In addition, the glass is designed to increase the annealing point and obtain the desired liquidus temperature. Select the existing product CorningLOTUS TM NXT glass served as a benchmark for the developments described in this disclosure.

[0102] Corning LOTUS TM NXT Glass (abbreviated as "Lotus" or "Lotus NXT"), as an existing product, is a premium glass solution designed to withstand high temperature processing requirements while providing industry-leading low total pitch variation (TPV). This results in brighter, more energy-efficient, higher-resolution displays for consumers and higher yields for panel manufacturers. Due to its thermal and dimensional stability, LOTUS TM NXT Glass is formulated to perform well in OLED and high-resolution LCD manufacturing processes and is ideal for the highest resolution LTPS displays and other applications requiring precision glass. It is well suited for processing temperatures up to 600°C.

[0103] The elastic modulus of the glasses provided by the present disclosure is up to 1% higher than that of Lotus NXT (existing glasses), and the SOC value is up to 2% lower than that of Lotus NXT. The annealing points of these glasses are also comparable to those of Lotus NXT, which will be beneficial to the overall TPV (total spacing variation). Overall, these glasses have similar compression behavior, higher Young's modulus and lower SOC compared to Lotus NXT, and are more advantageous from a manufacturing perspective because the 35kP temperature is lower, thereby extending the life of the isopipe, the 200P temperature is lower, thereby reducing the Pt temperature, reducing batch costs, and in many cases also increasing the liquidus viscosity. They are developed as potential alternatives to Lotus NXT, with the characteristics of reducing manufacturing costs and extending asset life. The lower 200P temperature allows less power to be put into the tank to melt the glass, thereby extending the life of the electrode. Lower temperatures also help to extend the life of refractory materials.

[0104] In the present disclosure, glasses were developed to improve the melting, forming, and liquidus properties of Lotus NXT while maintaining or improving customer-facing properties such as Young's modulus, SOC, and TPV (stress relaxation, compaction).

[0105] Lotus NXT has a strain point (fiber) of 752°C, an annealing point (fiber) of 806°C, a softening point (fiber) of 1,042.9°C, a coefficient of thermal expansion (CTE) of 34.8 at 0-300°C, and a density of 2.592 g / cm 3 , Poisson's ratio is 0.229, shear modulus is 33.64 GPa, elastic modulus is 82.70 GPa, stress optical coefficient (SOC) is 28.64, T(35kP) temperature is 1,296°C, and T(200P) temperature is 1,683°C.

[0106] Table 1 shows exemplary ranges of component contents and properties of the designed glasses, including minimum and maximum values ​​for component contents in exemplary glass compositions and their properties, including key properties such as annealing point, SOC, and elastic modulus. These glasses have properties similar to or better than Lotus NXT. These glasses also show a 17-29°C reduction in T(200P) temperature and a 4-16°C reduction in T(35kP) temperature. This reduction in temperature helps extend the life of the tank (Pt system) and isopipe, thereby reducing manufacturing costs. Many of these glasses exhibit a greater liquidus viscosity than NXT. This will reduce crystal growth on the edge guide of the isopipe during manufacturing, thereby reducing the downtime required for cleaning and rinsing to remove crystals. Crystals can cause defects in the glass sheet, so cleaning and rinsing are required to restore the sheet to a defect-free state.

[0107] Table 1.

[0108]

[0109]

[0110] In Table 1, SnO2 may be replaced with another suitable chemical fining agent as described herein.

[0111] According to some embodiments, the glasses or glass compositions provided herein include the following substances in mole percentages on an oxide basis:

[0112] SiO2: 66.17-74.31;

[0113] Al2O3: 11.72-13.86;

[0114] B2O3: 0.71-1.75;

[0115] MgO: 4.61-6.36;

[0116] CaO: 4.81-7.27;

[0117] SrO: 0.10-1.42; and

[0118] BaO:2.38-4.00.

[0119] According to some embodiments, the glasses or glass compositions provided herein include the following substances in mole percentages on an oxide basis:

[0120] SiO2: 69.65-70.77;

[0121] Al2O3: 12.34-13.20;

[0122] B2O3: 0.75-1.67;

[0123] MgO: 4.85-6.06;

[0124] CaO: 5.06-6.92;

[0125] SrO: 0.11-1.35; and

[0126] BaO:2.51-3.81.

[0127] Such glass is aluminoborosilicate glass. The aluminum oxide content is relatively high, for example, in the range of 12.34 to 13.20 mole percent. In some embodiments, SiO2 is in the range of 69.9 to 70.7 mole percent.

[0128] The glass composition may include an alkali metal oxide in an impurity amount. In some embodiments, the glass composition or glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O, and K2O of less than 0.1 mol.%, such as less than 0.09 mol.%, less than 0.08 mol.%, less than 0.07 mol.%, less than 0.06 mol.%, less than 0.05 mol.%, less than 0.04 mol.%, less than 0.03 mol.%, less than 0.02%, less than 0.01%, or 0%. In some embodiments, the glass composition has a combined concentration of Li2O, Na2O, and K2O of less than 0.06 mol.%.

[0129] In some embodiments, B2O3 is in a suitable range. For example, B2O3 is in the range of 0.75 to 1.75 mole percent, in the range of 0.75 to 1.67 mole percent, in the range of 0.75 to 1.60 mole percent, in the range of 0.75 to 1.50 mole percent, in the range of 0.75 to 1.40 mole percent, in the range of 0.75 to 1.30 mole percent, in the range of 0.75 to 1.20 mole percent, or in the range of 0.75 to 1.00 mole percent. In some embodiments, B2O3 is in the range of 0.75 to 1.00 mole percent.

[0130] In some embodiments, SrO is within a suitable range. For example, SrO is within a range of 0.11 to 1.42 mole percent, within a range of 0.11 to 1.40 mole percent, within a range of 0.11 to 1.35 mole percent, within a range of 0.11 to 1.30 mole percent, within a range of 0.11 to 1.20 mole percent, within a range of 0.11 to 1.10 mole percent, within a range of 0.11 to 1.00 mole percent, within a range of 0.11 to 0.90 mole percent, within a range of 0.11 to 0.80 mole percent, within a range of 0.11 to 0.70 mole percent, within a range of 0.11 to 0.60 mole percent, within a range of 0.11 to 0.50 mole percent, within a range of 0.11 to 0.40 mole percent, within a range of 0.11 to 0.30 mole percent, or within a range of 0.11 to 0.20 mole percent. In some embodiments, SrO is in the range of 0.11 to 1.00 or 0.50 mole percent.

[0131] In some embodiments, the ratio of RO / Al2O3 is in the range of 1.13 to 1.31, and RO is the sum of the molar percentages of MgO, CaO, SrO, and BaO. No ZnO is added to the glass. For example, in some embodiments, the ratio of RO / Al2O3 is in the range of 1.13 to 1.31.

[0132] The glass may further comprise 0.01 mol.% to 0.4 mol.% of a chemical fining agent selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br, or any combination thereof. For example, in some embodiments, the chemical fining agent comprises 0.08 mol.% to 0.14 mol.% SnO2.

[0133] In some embodiments, the glass composition may include impurity amounts of Fe2O3, ZrO2, or TiO2. Each of Fe2O3, ZrO2, and TiO2 may be in the range of 0 to 0.03 mole percent. In some embodiments, each of Fe2O3, ZrO2, and TiO2 may be zero or less than 0.01 mole percent.

[0134] The glass has a high annealing point, for example above 775° C. In some embodiments, the annealing point of the glass is in the range of 790° C. to 810° C., for example in the range of 790° C. to 806° C.

[0135] Glass also has a high elastic modulus (Young's modulus). For example, in some embodiments, the elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa.

[0136] The glass has a desired stress optical coefficient (SOC) that is relatively low compared to existing products. For example, the SOC of the glass is in the range of 26.70 to 30.59, such as in the range of 28.10 to 29.13.

[0137] The glass also has desirable low T(35kP) and T(200P) temperatures. For example, in some embodiments, the glass has a T(35kP) in the range of 1,280°C to 1,292°C, and a T(200P) in the range of 1,654°C to 1,666°C. T(35kP) and T(200P) represent the temperatures at which the viscosity of the glass is 35 kilopoise (kP) and 200 poise (P), respectively.

[0138] The liquidus viscosity of the glass is in a range of 100,000 poise to 250,000 poise, such as 120,000 poise to 250,000 poise, 150,000 poise to 250,000 poise, or 200,000 poise to 250,000 poise.

[0139] The glass also has suitable ranges of other properties, such as those shown in Table 1.

[0140] According to some embodiments, the glass provided by the present disclosure is an aluminoborosilicate glass and comprises the following substances in mole percentages on an oxide basis:

[0141] SiO2: 66.17-74.31;

[0142] Al2O3: 11.72-13.86;

[0143] B2O3: 0.75-1.20;

[0144] MgO: 4.61-6.36;

[0145] CaO: 4.81-7.27;

[0146] SrO: 0.11-0.5; and

[0147] BaO:2.38-4.00.

[0148] The elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa, and the stress optical coefficient (SOC) of the glass is in the range of 26.70 to 30.59.

[0149] According to some embodiments, the glass provided by the present disclosure is an aluminoborosilicate glass and comprises the following substances in mole percentages on an oxide basis:

[0150] SiO2: 69.65-70.77;

[0151] Al2O3: 12.34-13.20;

[0152] B2O3: 0.75-1.20;

[0153] MgO: 4.85-6.06;

[0154] CaO: 5.06-6.92;

[0155] SrO: 0.11-0.5; and

[0156] BaO:2.51-3.81.

[0157] The glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O, and K2O of less than 0.1 mol. %. In some embodiments, the glass composition has a combined concentration of Li2O, Na2O, and K2O of less than 0.06 mol. %.

[0158] In some embodiments, B2O3 is in the range of 0.75 to 1.20, such as 0.75 to 1.00 mole percent. SrO is in the range of 0.11 to 1.00, such as 0.11 to 0.50 mole percent.

[0159] The RO / Al2O3 ratio of the glass is in the range of 1.14 to 1.31, for example 1.20 to 1.31, and RO is the sum of the mole percentages of MgO, CaO, SrO and BaO.

[0160] The glass also includes 0.08 mol.% to 0.14 mol.% SnO2 as a chemical fining agent. In some embodiments, the glass composition may include impurity amounts of Fe2O3, ZrO2, or TiO2. Each of Fe2O3, ZrO2, and TiO2 may be in the range of 0 to 0.03 mol percent. In some embodiments, each of Fe2O3, ZrO2, and TiO2 may be zero or less than 0.01 mol percent.

[0161] The annealing point of the glass is in the range of 790° C. to 810° C., for example, in the range of 799° C. to 806° C. The elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa, and the stress optical coefficient (SOC) is in the range of 28.10 to 29.13.

[0162] In some embodiments, the glass has a T(35kP) in the range of 1,280°C to 1,292°C, and a T(200P) in the range of 1,654°C to 1,666°C.

[0163] The glass has other desirable properties as described herein.

[0164] The inventors have surprisingly found that compositions with specific oxide contents, such as low levels of B2O3 and SrO, particularly when combined with relatively high MgO contents and specific RO / Al2O3 ratios, can provide glasses with suitably high values ​​for high annealing point, high modulus, and low stress optical coefficient (SOC). The glasses exhibit desirable improvements over existing products such as Lotus NXT glass. The compositions described herein provide filled glass structures that provide lower stress optical coefficients.

[0165] In embodiments of the glass compositions described herein, SiO2 is the largest component in the composition and is therefore a major component of the glass network. SiO2 enhances the chemical durability of the glass, particularly the resistance of the glass composition to acid decomposition, and provides a desired liquidus temperature or liquidus viscosity. The resulting chemical durability makes the glass suitable for use as a flat panel display glass (e.g., AMLCD glass). Therefore, a high SiO2 concentration is generally required. However, if the SiO2 content is too high, the formability of the glass may be reduced because a higher concentration of SiO2 increases the difficulty of melting the glass, which in turn has an adverse effect on the formability of the glass.

[0166] In embodiments described herein, the glass composition includes SiO2 in an amount greater than or equal to about 69.65 mol.% and less than or equal to about 70.77 mol.%. In some embodiments, SiO2 is present in the glass composition in an amount greater than or equal to about 69.9 mol.% and less than or equal to about 70.7 mol.%.

[0167] The glass composition described herein also includes Al2O3. Al2O3 at a concentration equal to or greater than a certain amount (such as 12.34 mole percent) provides the glass with a low liquidus temperature and high viscosity, resulting in a high liquidus viscosity. The use of at least 12.34 mole percent of Al2O3 also increases the annealing point and modulus of the glass. Al2O3 increases the sensitivity of the glass to ion exchange strengthening. In addition, the addition of Al2O3 to the composition reduces the tendency of alkaline components (such as Na and K) (if any) to leach out of the glass, and therefore, the addition of Al2O3 increases the resistance of the composition to hydrolytic degradation. In addition, the addition of Al2O3 can also increase the softening point of the glass, thereby reducing the formability of the glass.

[0168] The glass compositions described herein include Al2O3 in an amount greater than or equal to about 12.34 mol.% and less than or equal to about 13.20 mol.%.

[0169] In some embodiments, in order to make the ratio of RO / Al2O3 in the range of 1.14 to 1.31, and RO is the sum of the molar percentages of MgO, CaO, SrO and BaO, when ZnO is not added, the content of Al2O3 is kept below 13.2%. For example, the ratio of RO / Al2O3 is in the range of 1.20 to 1.31.

[0170] B2O3 is both a glass former and a flux that helps melt and lowers the melting temperature. It has an effect on both the liquidus temperature and viscosity. Increasing B2O3 can be used to increase the liquidus viscosity of the glass. In order to achieve these effects, the glass composition of one or more embodiments may have a B2O3 concentration equal to or greater than 0.1 mole percent, such as equal to or greater than 0.75%. As discussed above with respect to SiO2, glass durability is very important for LCD applications. Durability can be controlled to a certain extent by increasing the concentration of alkaline earth oxides, and significantly reduced by increasing the B2O3 content. The annealing point decreases with the increase of B2O3, so it may be helpful to keep the B2O3 content low relative to its typical concentration in amorphous silicon substrates. Therefore, in some embodiments, the B2O3 concentration of the glass composition is in the range of about 0.75 to 1.67 mole percent. For example, B2O3 is in the range of 0.75 to 1.2 mole percent or 0.75 to 1.0 mole percent. Surprisingly, it was found that this low content of B2O3, combined with low SrO content and other oxides, increases the elastic modulus of the resulting glass and provides other properties as described herein, such as high annealing point, low stress optical coefficient, and reduced T(35kP) and T(200P). These properties make the glass easier to manufacture and also suitable for ultra-high resolution display applications such as 8K display technology.

[0171] In addition to the glass formers (SiO2, Al2O3, and B2O3), the glasses described herein also contain alkaline earth oxides. In some embodiments, four alkaline earth oxides are present in the glass composition, such as MgO, CaO, BaO, and SrO. Alkaline earth oxides provide various properties that are important for melting, clarification, forming, and final use of the glass. Therefore, in order to improve the performance of the glass in these aspects, in one embodiment, the ratio of (MgO+CaO+SrO+BaO) / Al2O3 is greater than or equal to 1.14. As this ratio increases, the viscosity tends to drop more than the liquidus temperature, so it becomes increasingly difficult to obtain a suitably high liquidus viscosity value. Therefore, in another embodiment, the ratio (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to 1.31.

[0172] The SrO content is low in the present disclosure. For example, SrO is in the range of 0.11 to 1.35 mole percent, in the range of 0.11 to 1.30 mole percent, in the range of 0.11 to 1.20 mole percent, in the range of 0.11 to 1.00 mole percent, or in the range of 0.11 to 0.50 mole percent, or any other range as described herein.

[0173] The reduced RO concentration and increased Al2O3 content are also factors that contribute to providing a filled glass structure, which reduces the stress optical coefficient of the resulting glass.

[0174] For certain embodiments, the alkaline earth oxides may be considered as components that are effectively single constituents. This is because their effects on viscoelastic properties, liquidus temperature, and liquidus phase relationships are qualitatively more similar to each other than their effects on the glass-forming oxides SiO2, Al2O3, and B2O3. However, the alkaline earth oxides CaO, SrO, and BaO can form feldspar minerals, particularly anorthite (CaAl2Si2O8) and celsium feldspar (BaAl2Si2O8) and their strontium-containing solid solutions, but the content of MgO in these crystals is not significant. Therefore, when the feldspar crystals are already in the liquidus phase, the super addition of MgO can be used to stabilize the liquid relative to the crystals, thereby reducing the liquidus temperature. At the same time, the viscosity curve generally becomes steeper, reducing the melting temperature, while having little effect on the low temperature viscosity. In this sense, the addition of a small amount of MgO is beneficial to melting because it can reduce the melting temperature; it is beneficial to forming because it can reduce the liquidus temperature and increase the liquidus viscosity while maintaining a high annealing point, thereby reducing the compaction degree. Thus, in various embodiments, the glass composition includes MgO in an amount ranging from about 4.85 mol percent to about 6.06 mol percent.

[0175] In addition to MgO, the glass composition also includes CaO in a range of about 5.06 mol % to about 6.92 mol %. These alkaline earth metal oxides in combination with other oxides including SiO2, Al2O3 and B2O3 in specific molar percentages provide the excellent properties described herein.

[0176] The presence of calcium oxide in the glass composition can produce a low liquidus temperature (high liquidus viscosity), a high annealing point and modulus, and a CTE in the most desirable range for flat panel applications, particularly AMLCD applications. The calcium oxide also helps improve chemical durability and is relatively inexpensive as a batch material compared to other alkaline earth oxides. However, at high concentrations, CaO increases density and CTE. In addition, at sufficiently low SiO2 concentrations, CaO can stabilize anorthite, thereby reducing liquidus viscosity. Therefore, in one embodiment, the CaO concentration can be between 5.06 mole percent and 6.92 mole percent.

[0177] Both SrO and BaO can result in low liquidus temperatures (high liquidus viscosities), and therefore, the glasses described herein will contain at least these two oxides. However, the selection and concentration of these oxides are selected to avoid increases in CTE and density and decreases in modulus and annealing point. The relative proportions of SrO and BaO can be balanced to obtain a combination of appropriate physical properties and liquidus viscosities so that the glass can be formed by a down-draw process. In some embodiments, the glass contains SrO in the range of about 0.11 mole percent to about 1.35 mole percent, and BaO in the range of about 2.51 mole percent to about 3.81 mole percent. In some embodiments, SrO is less than 1 mole percent.

[0178] In addition to meltability and annealing point considerations, for AMLCD applications, the CTE of the glass should be compatible with the CTE of silicon. To achieve such CTE values, the exemplary glass controls the RO content of the glass. For a given Al2O3 content, controlling the RO content is equivalent to controlling the RO / Al2O3 ratio.

[0179] In one or more embodiments, the present disclosure provides glasses for AMLCD applications having a coefficient of thermal expansion (CTE) (0-300° C.) of about 34.1 x 10 -7 / ℃ to about 37.3x10 -7 / °C (i.e., in the range of about 3.41 ppm / °C to about 3.73 ppm / °C).

[0180] Glass can be formed by a down-draw process (e.g., a fusion process), which means that the liquidus viscosity of the glass needs to be relatively high. Individual alkaline earths play an important role in this regard, and they may destabilize the crystalline phase that would otherwise form. BaO and SrO are particularly effective in controlling the liquidus viscosity and are included in the exemplary glasses at least for this purpose. As shown in the examples given below, a combination of four alkaline earth oxides will produce a glass with a high liquidus viscosity, where the sum of the alkaline earths meets the RO / Al2O3 ratio constraints required to achieve a low melting temperature, a high annealing point, and a suitable CTE.

[0181] In addition to the above components, the glass compositions described herein may also include various other oxides to adjust various physical, melting, clarifying and forming properties of the glass. Examples of such other oxides include, but are not limited to, TiO2, MnO, Fe2O3, ZnO, Nb2O5, MoO3, ZrO2, Ta2O5, WO3, Y2O3, La2O3 and CeO2. In some embodiments, these oxides are not added. In some embodiments, the amount of each of these oxides may be less than or equal to 0.5 mole percent, such as less than 0.1 mole percent, including zero percent, and their total combined concentration may be less than or equal to 2.0 mole percent, such as less than 1.0 mole percent. In some embodiments, the total combined concentration of these oxides is the amount of impurities, for example, less than 0.1 mole percent.

[0182] The glass compositions described herein may also include various contaminants associated with the batch materials and / or introduced into the glass by the melting, refining and / or forming equipment used to produce the glass, particularly Fe2O3 and ZrO2. The glass may also contain SnO2 as a result of Joule melting using tin oxide electrodes and / or by the dosing of tin-containing materials such as SnO2, SnO, SnCO3, and SnC2O2. In some embodiments, the glass is substantially free of or free of Fe2O3, TiO2, and ZrO2.

[0183] As2O3 and Sb2O3 are effective high temperature fining agents for AMLCD glass. However, due to their toxicity, they require special handling during the glass manufacturing process.

[0184] Example

[0185] The following examples are listed below to illustrate the methods and results according to the disclosed subject matter. These examples are not intended to include all embodiments of the subject matter disclosed herein, but are intended to illustrate representative methods and results. These examples are not intended to exclude equivalents and variants of the present disclosure, which should be apparent to those skilled in the art.

[0186] Efforts have been made to ensure the accuracy of numbers (e.g., amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise indicated, temperatures are in ° C. or are room temperature, and pressures are equal to or close to atmospheric pressure. The compositions themselves are given as mole percentages based on oxides and have been standardized to 100%. There are many variations and combinations of reaction conditions, such as component concentrations, temperatures, pressures, and other reaction ranges and conditions that can be used to optimize the product purity and yield obtained from the process. Only reasonable routine experiments are required to optimize these process conditions.

[0187] The glass properties listed in the table are determined according to conventional techniques in the glass field. Therefore, the linear coefficient of thermal expansion (CTE) in the temperature range of 25-300°C is expressed as x10 -7 / ° C, and the annealing point is expressed in ° C. These are determined by the fiber elongation technique (ASTM reference E228-85 and C336 respectively). The density (in grams / cm 3 The melting temperature (defined as the temperature at which the glass melt exhibits a viscosity of 200 poise) in units of °C was calculated by fitting the high temperature viscosity data measured by the rotating cylinder viscometry method (ASTM C965-81) using the Fulcher equation.

[0188] The viscosity of glass at elevated temperatures is measured in accordance with ASTM C965-96 (2012) entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point". As used herein, the "Vogel-Fulcher-Tamman" (VFT) relationship describes the temperature dependence of viscosity and is represented by the following formula:

[0189] logη=A+B T-To

[0190] Where η is the viscosity. To determine VFT A, VFT B and VFT T o , the viscosity of the glass composition is measured within a given temperature range. The raw data of viscosity and temperature are then fitted to the VFT formula by least squares fitting to obtain A, B and T o Using these values, the viscosity point at any temperature above the softening point can be calculated (eg, 200 Poise (P) temperature, 35,000P temperature, and 200,000P temperature).

[0191] The liquidus temperature (in °C) of the glass is measured using the standard gradient boat liquidus method of ASTM C829-81. This involves placing crushed glass particles in a platinum boat, placing the boat in a kiln with gradient temperature zones, heating the boat in the appropriate temperature zones for 24 hours, and determining by microscopic examination the highest temperature at which crystals appear inside the glass. More specifically, the glass sample is removed from the Pt boat in one piece and examined using a polarized light microscope to determine the location and nature of crystals formed at the Pt and air interface and inside the sample. Because the gradient of the kiln is very well defined, the relationship between temperature and location can be well estimated to within 5-10 °C. The temperature at which crystals are observed inside the sample is taken as the liquidus of the glass (for the corresponding test period). Tests are sometimes run for longer periods of time (e.g., 72 hours) to observe slower growth phases. The liquidus viscosity (in poise) is determined from the liquidus temperature and the coefficients of Fulcher's formula.

[0192] Values ​​of Young's modulus and shear modulus (in GPa) and Poisson's ratio were determined using a resonant ultrasonic spectroscopy technique of the general type specified in ASTM E1875-00el.

[0193] Stress-optical coefficient (SOC) values ​​may be measured as described in Procedure C (Glass Disk Method) of ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient."

[0194] Table 2-8 shows exemplary glasses including samples 1-42. As can be seen from Table 2-8, the exemplary glasses have such density, annealing point, Young's modulus, CTE, and stress optical coefficient (SOC) that the glasses are suitable for display applications, such as AMLCD substrate applications, and more specifically for low temperature polysilicon and oxide thin film transistor applications. Although not shown in Table 2-8, the durability of the glasses in acidic and alkaline media is similar to that of glasses obtained from commercial AMLCD substrates, and therefore is suitable for AMLCD applications. The exemplary glasses can be formed using a down-draw technique and are compatible with fusion processes, in particular, by the above-mentioned criteria.

[0195] The exemplary glasses in the table were prepared using commercial sand as the silica source, ground so that 90% by weight of the glass would pass through a standard U.S. 100 mesh sieve. Alumina was the source of alumina, periclase was the source of MgO, limestone was the source of CaO, strontium carbonate, strontium nitrate, or a mixture thereof was the source of SrO, barium carbonate was the source of BaO, and tin (IV) oxide was the source of SnO2. The raw materials were thoroughly mixed, loaded into a platinum container suspended in a kiln heated by a silicon carbide heating rod, melted at a temperature of 1600 to 1650°C and stirred for several hours to ensure homogeneity, and delivered through a hole in the bottom of the platinum container. The resulting glass mass was annealed at or near the annealing point, and the physical, viscosity, and liquidus properties were determined using various experimental methods.

[0196] These methods are not exclusive, and the glasses of Tables 1-8 can be prepared using standard methods well known to those skilled in the art. Such methods include continuous melting processes, such as those carried out in a continuous melting process, wherein the melter used in the continuous melting process is heated by gas, electricity, or a combination thereof.

[0197] Raw materials suitable for producing exemplary glasses include commercial sand as a source of SiO2; aluminum oxide, aluminum hydroxide, hydrated aluminum oxide, and various aluminosilicates, nitrates, and halides as a source of Al2O3; boric acid, anhydrous boric acid, and boric oxide as a source of B2O3; periclase, dolomite (also a source of CaO), magnesium oxide, magnesium carbonate, magnesium hydroxide, and various forms of magnesium silicates, aluminosilicates, nitrates, and halides as a source of MgO; limestone, aragonite, dolomite (also a source of MgO), wollastonite, and various forms of calcium silicates, aluminosilicates, nitrates, and halides as a source of CaO; and oxides, carbonates, nitrates, and halides of strontium and barium. If a chemical fining agent is desired, tin can be added as SnO2, as a mixed oxide with another major glass component (e.g., CaSnO3), or under oxidizing conditions as SnO, tin oxalate, tin halide, or other tin compounds known to those skilled in the art.

[0198] The glasses in Tables 1-8 contain SnO2 as a clarifier, but other chemical clarifiers may also be used to obtain glass of sufficient quality for TFT substrate applications. For example, the exemplary glass may employ any one or combination of As2O3, Sb2O3, CeO2, Fe2O3, and halides as intentional additions to promote clarification, and any of these may be used in combination with the SnO2 chemical clarifier shown in the examples. Among them, As2O3 and Sb2O3 are generally considered hazardous materials and are controlled in waste streams that may be generated during glass manufacturing or during TFT panel processing. Therefore, it is desirable to limit the concentration of As2O3 and Sb2O3, either individually or in combination, to no more than 0.005 mol%.

[0199] In addition to the elements intentionally added to the exemplary glasses, almost all stable elements in the periodic table are present in the glass at some level, either through low-level contamination in the raw materials, through high-temperature attack of refractory materials and precious metals during manufacturing, or through the intentional introduction of low-level elements to fine-tune the properties of the final glass. For example, zirconium can be introduced as a contaminant through interaction with zirconium-rich refractory materials. As another example, platinum and rhodium can be introduced through interaction with precious metals. As another example, iron can be introduced into the raw materials as an impurity, or it can be intentionally added to enhance control of gaseous inclusions. As another example, manganese can be introduced to control color or enhance control of gaseous inclusions.

[0200] As another example, for combined concentrations of Li2O, Na2O, and K2O, alkali metals may be present as impurity components at levels up to about 0.1 mol%.

[0201] Hydrogen inevitably forms in the form of hydroxyl anions OH - , and its presence can be determined by standard infrared spectroscopy techniques. Dissolved hydroxide ions have a significant and nonlinear effect on the annealing point of the exemplary glass, so in order to obtain the desired annealing point, it may be necessary to adjust the concentration of the main oxide component to compensate. The concentration of hydroxide ions can be controlled to some extent by selecting the raw materials or selecting the melting system. For example, boric acid is a major source of hydroxyl groups, and replacing boric acid with boric oxide can be a useful means of controlling the concentration of hydroxyl groups in the final glass. The same applies to other potential raw materials, including hydroxide ions, hydrates, or compounds containing physically adsorbed or chemically adsorbed water molecules. If a burner is used in the melting process, then hydroxide ions can also be introduced through the combustion products of the combustion of natural gas and related hydrocarbons, so it may be necessary to transfer the energy used in the melting from the burner to the electrode to compensate. Alternatively, one can use an iterative process to adjust the main oxide component to compensate for the deleterious effects of dissolved hydroxide ions.

[0202] Sulfur is commonly present in natural gas and is also an impurity component of many carbonate, nitrate, halide and oxide raw materials. In the form of SO2, sulfur can be a source of troublesome gaseous inclusions. The tendency to form SO2-rich defects can be controlled to a great extent by controlling the sulfur content of the raw materials and by adding low levels of relatively reducing multivalent cations to the glass matrix. While not wishing to be bound by theory, it appears that SO2-rich gaseous inclusions are primarily formed by reducing sulfate (SO4) dissolved in the glass. = ) is produced.

[0203] Increasing the concentration of barium in the exemplary glass appears to increase the retention of sulfur in the glass during the early stages of melting, but as noted above, barium is required to achieve a low liquidus temperature and thus a high T. 35k -T liq and high liquidus viscosity. Intentionally controlling the sulfur level in the raw materials to a lower level is a useful means of reducing dissolved sulfur (possibly sulfate) in the glass. In particular, sulfur is preferably less than 200 ppm by weight in the batch, more preferably less than 100 ppm by weight in the batch.

[0204] The reduced multivalent states can also be used to control the tendency of the exemplary glasses to form SO2 bubbles. While not wishing to be bound by theory, these elements act as potential electron donors, suppressing the electromotive force of sulfate reduction. Sulfate reduction can be written as a half-reaction such as

[0205] SO4 = →SO2+O2+2e -

[0206] where e - represents electrons. The "equilibrium constant" for the half-reaction is

[0207] K eq =[SO2][O2][e - ] 2 / [SO4 = ]

[0208] The brackets indicate chemical activity. Ideally, one would like to force the reaction so that SO2, O2, and 2e - Sulfate is formed. Adding nitrates, peroxides, or other oxygen-rich raw materials may help, but may also be detrimental to the reduction of sulfates in the early stages of melting, which may offset the benefits of adding them. SO2 has very low solubility in most glasses, so it is impractical to add to the glass melt. Electrons can be "added" by reducing multivalent states. For example, ferrous iron (Fe 2+ ) is represented by the appropriate electron-donating half-reaction

[0209] 2Fe2+ →2Fe 3+ +2e -

[0210] This "activity" of electrons can force the sulfate reduction reaction to proceed to the left, thereby stabilizing the SO4 in the glass. = Suitable reducing polyvalents include, but are not limited to, Fe 2+ , Mn 2+ Sn 2+ , Sb 3+ 、As 3+ 、V 3+ 、Ti 3+ and others familiar to those skilled in the art. In each case, it is important to minimize the concentration of such components to avoid deleterious effects on the color of the glass or, in the case of As and Sb, to avoid adding such components at levels high enough to avoid complicating waste management in the end user's process.

[0211] In addition to the major oxide components of the exemplary glasses and the minor or impurity components described above, there may be varying levels of halides present, either as contaminants introduced by the choice of raw materials or as intentional components used to eliminate gaseous inclusions in the glass. Halides may be added at levels of about 0.4 mol% or less as fining agents, but it is generally desirable to use lower amounts if possible to avoid corrosion of exhaust gas treatment equipment. In some embodiments, the concentration of the individual halide elements is less than about 200 ppm by weight for each individual halide, or less than about 800 ppm by weight for the sum of all halide elements.

[0212] In addition to these major oxide components, minor and impurity components, multivalents and halide fining agents, it may be useful to add other colorless oxide components in low concentrations to achieve desired physical, optical or viscoelastic properties. Such oxides include, but are not limited to, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5, MoO3, WO3, ZnO, In2O3, Ga2O3, Bi2O3, GeO2, PbO, SeO3, TeO2, Y2O3, La2O3, Gd2O3 and others known to those skilled in the art. By an iterative process of adjusting the relative proportions of the major oxide components of the exemplary glasses, such colorless oxides may be added to levels up to about 2 mol% without affecting the annealing point, T 35k -T liq or liquidus viscosity has an unacceptable effect.

[0213] The samples and their data are summarized in Tables 2-8.

[0214] In the table, the lowest isothermal temperature range (temperature range <2% internal crystals) is the lowest temperature at which the percentage of crystallinity inside or on the Pt interface is less than 2%. This lowest isothermal temperature range is the lowest temperature at which crystals are found in the glass during the 72-hour isothermal hold. The symbol (--) means not tested yet.

[0215] Table 2 shows examples of glass (samples 1-6)

[0216] Table 2.

[0217]

[0218]

[0219] Table 3 shows examples of glass (samples 7-12) Table 3.

[0220]

[0221]

[0222]

[0223] Table 4 shows examples of glass (samples 13-18) Table 4.

[0224]

[0225]

[0226] Table 5 shows examples of glass (samples 19-24) Table 5.

[0227]

[0228]

[0229]

[0230] Table 6 shows examples of glass (Samples 25-30).

[0231] Table 6.

[0232]

[0233]

[0234] Table 7 shows examples of glass (samples 31-36) Table 7.

[0235]

[0236]

[0237]

[0238] Table 8 shows examples of glass (samples 37-42) Table 8.

[0239]

[0240]

[0241] Figure 1 Annealing point results are shown for different mole percentages of B2O3 in the glass composition. Higher annealing points due to lower B2O3 result in improved or lower stress relaxation.

[0242] The glass and composition provided by the present disclosure have significant advantages. For example, the glass composition exhibits desirable physical and chemical properties, such as a high annealing point (e.g., above 790° C.), a high elastic modulus, a low stress optical coefficient (SOC), and a desired liquidus viscosity. The glass composition is suitable for use as a substrate in a flat panel display device such as an active matrix liquid crystal display (AMLCD) with ultra-high resolution under, for example, 8K display technology.

[0243] In another aspect, the present disclosure provides an article comprising the glass or glass composition described herein. For example, a substrate for a liquid crystal display includes the glass or glass composition described herein.

[0244] In another aspect, the present disclosure provides a flat panel display device comprising at least one sheet comprising glass as described herein. Such a device may include a polysilicon thin film transistor.

[0245] In another aspect, a method for producing a glass or glass composition as described herein is provided. Such a method comprises at least one step of mixing and melting raw materials in mole percentages based on oxides to provide the oxides. Such a method may also comprise making a sheet comprising the glass composition by a down-drawn sheet manufacturing process or a fusion process.

[0246] Although the subject matter has been described in terms of exemplary embodiments, it is not limited thereto. Rather, the appended claims should be interpreted broadly to include other variations and embodiments that may be made by those skilled in the art.

Claims

1. A glass comprising the following substances in molar percentages based on oxides: SiO2: 66.17-74.31; Al2O3: 11.72-13.86; B2O3: 0.71-1.75; MgO: 4.61-6.36; CaO: 4.81-7.27; SrO: 0.10-1.42; and BaO: 2.38-4.00, The glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%.

2. The glass of claim 1, wherein the glass comprises, in mole percentages on an oxide basis: SiO2: 69.65-70.77; Al2O3: 12.34-13.20; B2O3: 0.75-1.67; MgO: 4.85-6.06; CaO: 5.06-6.92; SrO: 0.11-1.35; and BaO:2.51-3.

81.

3. The glass of claim 1, wherein B2O3 is in the range of 0.75 to 1.50 mole percent.

4. The glass of claim 1, wherein B2O3 is in the range of 0.75 to 1.20 mole percent.

5. The glass of claim 1, wherein SrO is in the range of 0.11 to 1.00 mole percent.

6. The glass of claim 1, wherein SrO is in the range of 0.11 to 0.50 mole percent.

7. The glass of any one of claims 1 to 6, wherein the ratio of RO / Al2O3 is in the range of 1.14 to 1.31, and RO is the sum of the molar percentages of MgO, CaO, SrO and BaO.

8. The glass according to any one of claims 1 to 6, wherein the ratio of RO / Al2O3 is in the range of 1.20 to 1.

31.

9. The glass according to any one of claims 1 to 6, further comprising 0.01 mol.% to 0.4 mol.% of a chemical fining agent selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br or any combination thereof.

10. The glass of claim 9, wherein the chemical fining agent comprises 0.08 mol. % to 0.14 mol. % SnO2.

11. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 790°C to 810°C.

12. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 799°C to 806°C.

13. The glass of any one of claims 1 to 6, wherein the glass has an elastic modulus in the range of 83.30 GPa to 84.49 GPa.

14. The glass of any one of claims 1 to 6, wherein the glass has a stress optical coefficient (SOC) in the range of 26.70 to 30.

59.

15. The glass of any one of claims 1 to 6, wherein the glass has a stress optical coefficient (SOC) in the range of 28.10 to 29.

13.

16. The glass of any one of claims 1 to 6, wherein T(35kP) of the glass is in the range of 1,280°C to 1,292°C, and T(200P) is in the range of 1,654°C to 1,666°C, and T(35kP) and T(200P) represent the temperatures at which the viscosity of the glass is 35 kilopoise (kP) and 200 poise (P), respectively.

17. A glass comprising, in mole percentages on an oxide basis: SiO2: 66.17-74.31; Al2O3: 11.72-13.86; B2O3: 0.75-1.20; MgO: 4.61-6.36; CaO: 4.81-7.27; SrO: 0.11-0.5; and BaO: 2.38-4.00, wherein the glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%, The elastic modulus of the glass is in the range of 83.30 GPa to 84.49 GPa, and The stress optical coefficient (SOC) of the glass is in the range of 26.70 to 30.

59.

18. The glass of claim 17, wherein the glass comprises, in mole percentages on an oxide basis: SiO2: 69.65-70.77; Al2O3: 12.34-13.20; B2O3: 0.75-1.20; MgO: 4.85-6.06; CaO: 5.06-6.92; SrO: 0.11-0.5; and BaO:2.51-3.

81.

19. The glass of claim 17, wherein B2O3 is in the range of 0.75 to 1.0 mole percent.

20. The glass of any one of claims 17 to 19, wherein the ratio of RO / Al2O3 is in the range of 1.20 to 1.31, and RO is the sum of the mole percentages of MgO, CaO, SrO and BaO.

21. The glass according to any one of claims 17 to 19, further comprising 0.08 mol.% to 0.14 mol.% SnO2 as a chemical fining agent.

22. The glass of any one of claims 17 to 19, wherein each of Fe2O3, ZrO2, and TiO2 is in the range of 0 to 0.03 mole percent.

23. The glass of any one of claims 17 to 19, wherein the stress optical coefficient (SOC) is in the range of 28.10 to 29.

13.

24. The glass of any one of claims 17 to 19, wherein T(35kP) of the glass is in the range of 1,280°C to 1,292°C, and T(200P) is in the range of 1,654°C to 1,666°C, and T(35kP) and T(200P) represent the temperatures at which the viscosity of the glass is 35 kilopoise (kP) and 200 poise (P), respectively.

25. An article comprising the glass of any one of claims 1 to 6. 26 . A liquid crystal display substrate, comprising the glass according to claim 1 .

27. A flat panel display device comprising at least one plate comprising the glass according to any one of claims 1 to 6, and a polysilicon thin film transistor.

28. A method for producing the glass of any one of claims 1 to 6, comprising mixing and melting raw materials in mole percentages on an oxide basis.

29. The method of claim 28, further comprising manufacturing the sheet comprising glass by a down-drawn sheet manufacturing process or a fusion process.

Citation Information

Cited By

  • Preparation method of high-transmittance impact-resistant glass based on rapid annealing technology

    CN120647138A